Performance Analysis of Physical Education Teachers Certificated and Not Certificated - Joan Rhobi Andrianto (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
This study aims to describe the performance of Physical Education teachers at the unit level of Public Elementary Schools throughout the Kesamben District, Jombang Regency in 2022/2023. This research method uses a type of quantitative research. The subjects in this study were all Physical Education teachers in Gugus I Public Elementary Schools throughout the Kesamben District, Jombang Regency, with a total of 17 teachers. Obtaining the percentage score for each competency is then converted to a value scale of 1, 2, 3, or 4. After that, the values are added up, then converted into a scale of 100. The next step is to determine the criteria for the value obtained ≤ 50 (less), 51-60 ( moderate), 61-75 (fair), 76-90 (good), 91-100 (very good). Based on the results of data analysis, there is a comparison of Physical Education Teachers in Elementary Schools in the Kesamben District, Jombang Regency, who are certified to get the best PKG score with a total score of 81, or get a score of 91 on a scale of 100 with the very good category. The lowest PKG with a total score of 64, or a score of 73 on a scale of 100. While the average PKG score is 76 on a scale of 100, with the (good) category. While those who have not been certified, the highest PKG score is 70. And the lowest PKG score is 66. Meanwhile, the average is 68 in the (sufficient) category. The conclusion in this study is that physical education teachers at SDN Kesamben District, Jombang Regency have significant differences in the results of PKG scores between teachers who have been certified and those who have not been certified. Certified teachers only have deficiencies in professional competency assessment, while teachers who have not been certified have deficiencies in social assessment and competence.